The role of parents in educating children on the values of religious moderation in the digital era - Muchamad Rynaldi Cahyo; Muhammad Syakur; M. Jamal; Muh. Baehaqi; Sumarjoko; Husna Nashihina (At Turots: Jurnal Pendidikan Islam, 2024)
The digital era poses unprecedented challenges to family resilience, particularly concerning the rapid and often unfiltered flow of religious information that potentially triggers intolerant attitudes and radicalization among the younger generation. This study aims to analyze the strategic role of parents in educating children on religious moderation values (wasathiyah) amidst the rising phenomenon of cyber-religion. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation focusing on urban Muslim families who actively engage with digital media. The findings indicate that the parental role has undergone a significant transformation from traditional educators to digital gatekeepers and providers of digital modeling. Parents internalize four foundational pillars of moderation: tolerance (tasamuh), non-violence, balance (tawazun), and an accommodative stance toward local culture. These mentoring strategies are implemented through dialogic, two-way communication rather than one-way instructions, alongside the reinforcement of the Tabayyun (information verification) principle as a crucial basis for Islamic digital literacy. However, this study also identifies a critical digital gap—a competence disparity between generations—that creates an "authority vacuum," allowing anonymous virtual religious influencers to exert greater influence over children’s mindsets than their own parents. This phenomenon is further complicated by the use of appealing visual aesthetics in radical content that targets the youth's lifestyle. The study concludes that while family is the madrasah al-ula, systemic collaboration between families, educational institutions, and the government is essential to build children's cognitive resilience against digital radicalism. These findings suggest that digital literacy policies must integrate religious moderation values to effectively safeguard the social-religious identity of the next generation in a globalized digital landscape.